Studi Kompetensi Paedagogik Guru Pendidikan Al-Islam Dan Kemuhammadiyahan SMP Muhammadiyah 1 Surakarta Tahun Pelajaran 2015/2016 - Putra Tamtama, Taufiqurrahmat; , Drs. Zaenal Abidin, M.Pd (2016)
One determinant of success in education is the role of a teachers. Because the teachers is the figure who interact directly with learners in the learning activities are processed. Therefore teachers should be required to have the pedagogic competence, that teachers are able to carry out active learning, innovative, creative and fun. The problem of the research is how the competence of pedagogic teachers Education Al-Islam and Kemuhammadiyahan Junior High School Muhammadiyah 1 Surakarta Years Lessons 2015/2016. This research aims to identify the competence of pedagogic Teachers Education and Kemuhammadiyahan Al-Islam. As for the result of this research area expected to contribute to the thinking that is constructive for the pedagogic competence education teachers progres Al-Islam and Kemuhammadiyahan, as well as material inputs in order to created a new atmosphere in the activity of active learning, innovative, creative, effective, and fun amongst educators with lernes. This type of research is research field with data source from teachers Education Al-Islam and Kemuhammadiyahan, the head of the school, the students, and in Junior High School Muhammadiyah 1 Surakarta. The methods used in data collection is interviews, documentation, and observations. While the method of data analysis used is descriptive qualitative. The research result showed that Teachers Education Al-Islam and Kemuhammadiyahan Junior High School Muhammadiyah 1 Surakarta Lessons Year 2015/2016 has met all aspect along with indicator-indicator of understanding, namely pedagogic competence of learnes, learning and mastering the principles of learning that educate, curriculum development, educational learning activities, development of potential learnes, communication with learner, assessment an evaluation. Keywords: Pedagogic, Teacher Competence, Education and Kemuhammadiyahan Al-Islam